PROTECTIVE EFFECT OF CAMELLIA SINENSIS L. AGAINST OXIDATIVE STRESS AND INTESTINAL DYSBIOSIS INDUCED BY A HIGH-FAT DIET IN WISTAR RATS - Benaraba, Rachida; Benguiar, Rachida; Ouattara Tindjo, Joceline Julia; Fiche , Nabila; Benguelloula , Imane; Hemida, Houari; Daboné , Denis (Food and Feed Research, 2026)
The purpose of this study is to assess the effect of green tea (Camellia sinensis L.), integrated into the diets of rats, against the emergence of obesity and its nutritionally induced complications. 24 Wistar rats were divided into 4 groups. Groups 1 (control) and 2 (SGT) were subjected to a standard diet alone or supplemented with green tea. Group 3 (HF) received a high-fat diet alone, however, Group 4 (HFGT) was subjected to the same diet supplemented with green tea. After 16-weeks experimentation period, biochemical and oxidative analyses on the plasma and tissue levels were performed, which were complemented by the enumeration of certain bacteria from the intestinal microbiota. The results revealed that the high-fat diet induced an19% and 156% increase in body weight and adipose tissue weight in rats,repectively. It also stimulated a significant increase in plasma levels of blood glucose (53%), Triglycerides (27%). This diet affected the antioxidant status, inducing a decrease estimated at 48%  in reducing power on the plasma level, at 38% of the hepatic level, and at 55% of the cardiac level. Thus, a reduction in thiol groups was observed at the renal (41%), cardiac (60%), and plasma (58%) levels. This diet promotes lipid accumulation in the liver, thus causing steatosis. All these metabolic imbalances restored by green tea supplementation. Indeed, the group of rats fed a high-fat diet supplemented with 2% tea showed a 16%  and 48% reduction in their body weight and adipose tissue mass, respectively . Green tea restored blood sugar levels by 35% and triglycerides by 11%. It exertd an antioxidant effect by increasing the plasma reducing power by 37%, hepatic by 22%, and cardiac by 34%. The level of thiol groups in the heart and plasma has been restored, with an increase of (34%) and (50%) respectively. This plant had the ability to inhibit the formation of lipid vacuoles induced by the high-fat diet. Also, the incorporation of green tea into the high-fat diet reduced the number of E.coli and Bacteroides spp. and increased the concentration of Lactobacillus spp. in the HFGT group compared to the SGT group. All these results indicated that green tea can be considered in new preventive nutritional approaches to explore, aimed at modulating biochemical and oxidative disorders and intestinal dysbiosis in the context of obesity.
Keywords: Obesity, Green tea (Camellia sinensis L.), High-fat diet, Oxidative stress, Gut microbiota.